Eventos adversos relacionados à gravidade e carga de trabalho de enfermagem em Unidade de Terapia Intensiva - Serafim, Clarita Terra Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Adverse events (AEs) have been widely used as a quality assessment tool of health care as they offer the possibility of monitoring and comparisons over time. The nursing workload, as well as the severity of the patients' disease may be related to the incidence of AEs. Thus, this study aimed to identify the incidence of AEs and relate it to the severity of the patients' disease and to the workload of the nursing staff in an intensive care unit (ICU) in Sao Paulo. This is an exploratory quantitative study where it was conducted a prospective descriptive analysis. The sample consists of 138 subjects. The data were collected at a University hospital in a city in the interior of Sao Paulo in the period of June and July of 2014, using the instruments SAPS 3, applied to the first hour of hospitalization, and NAS through clinical visits, on duty passages and medical records. To record the AEs, it was created a data collection worksheet based on the Nursing Indicators Manual published by the Commitment Program in Hospital Quality applicable to the ICU. The patients who stayed less than 24 hours in the hospital and those who were readmitted were excluded from the study. This study was approved by the Ethics Committee under the number CAEE 26365014600005411. On a total of 138 subjects, average age of 58.8 years old, 58% were male. During the study, there were 166 AEs in which 15 were related to medication errors and 151 to other types of AEs, 29.5% were related to pressure ulcers, 29.8% related to skin lesions, followed by 21.9% unplanned removal of the feeding tube. The average severity assessed by the SAPS 3 was 62.6%, and the average nursing workload in 800 checks was 66.8%. The ratio between incidence and severity of AEs patients was directly significant, while the nursing workload was conversely significant; demonstrating that the higher the nursing work-load, less incidence of AEs will exist. We conclude that the incidence of AEs and the ...

Eventos adversos (EAs) têm sido amplamente utilizados como instrumento de avaliação de qualidade da assistência à saúde, pois oferecem a possibilidade de acompanhamento e comparações ao longo do tempo. A carga de trabalho da enfermagem, assim como a gravidade do paciente podem estar relacionadas à incidência de EAs. Em vista disto, este estudo teve por objetivo identificar a incidência dos EAs e relacioná-la à gravidade do paciente e à carga de trabalho da equipe de enfermagem, em uma Unidade de Terapia Intensiva (UTI) do interior paulista. Trata-se de um estudo quantitativo exploratório, prospectivo de análise descritiva. A amostra constitui-se por 138 sujeitos. Os dados foram coletados em um hospital universitário do interior paulista, nos meses de junho e julho de 2014, por meio dos instrumentos SAPS 3, aplicado na primeira hora de internação, e NAS por meio de participação em visitas clínicas, passagem de plantão e leituras de prontuários. Para o registro de EAs criou-se uma planilha de coleta de dados própria, com base no Manual de Indicadores de Enfermagem publicado pelo Programa de Compromisso em Qualidade Hospitalar, aplicáveis à UTI. Excluiu-se do estudo pacientes que permaneceram por tempo inferior a 24 horas e aqueles readmitidos. A aprovação do estudo pelo Comitê de Ética tem o número CAEE 26365014600005411. Do total de 138 sujeitos, a idade média foi de 58,8 anos, sendo 58% do sexo masculino. No período do estudo houve 166 EAs, dos quais 15 estavam relacionados a erros de medicação e 151 aos demais tipos de EAs, sendo 29,5% relacionados à úlceras por pressão, 29,8% relacionados às lesões de pele, seguidos de 21,9% de saída não planejada de sonda oro/nasogastro-enteral. A média de gravidade avaliada pelo SAPS 3, foi de 62,6 pontos e carga de trabalho de enfermagem média, em 800 verificações, obteve índice de 66,8%. A relação entre a incidência de EAs e a gravidade do paciente...
Adverse events related to the severity and nursing workload in Intensive Care unit
Keywords: Cuidados com os doentes; Indicadores de qualidade em assistência à saúde; Horário de trabalho - Avaliação; Unidade de tratamento intensivo; Enfermagem; Nursing; Hours of labor - Evaluation